Emerging technologies in computer engineering : microservices in big data analytics : second International Conference, ICETCE 2019, Jaipur, India, February 1-2, 2019, Revised selected papers /: microservices in big data analytics : second International Conference, ICETCE 2019, Jaipur, India, February 1-2, 2019, Revised selected papers. (2019) - Unknown
No abstract available